Dynamics in IgM and IgG antibodies against a polysaccharide capsule-containing complex of various S. pneumonia and H. influenza type b serotypes in children with chronic lung and bronchial inflammatory diseases after vaccination with “Pneumo-23” and “Act-HIB” - E. S. Korovkina (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
A lead place among pathogens resulting in pediatric chronic bronchopulmonary diseases is held by S. pneumoniae and Haemophilus influenzae. Vaccination against pneumococcal and hemophilic infections is approved and recommended for patients with chronic pathologies, but no clear recommendations for combined use of Pneumo-23 and Act-HIB vaccines in children with congenital pulmonary malformations and bronchial asthma were proposed.Materials and methods. There were enrolled 92 children aged 0–17 years old with chronic bronchopulmonary diseases; 55 healthy children, and 57 unvaccinated children with chronic broncho-pulmonary pathology were included into control group. Mono- and combination vaccination by Pneumo-23 and/or Act-HIB was performed in remission period. IgM and IgG level against H. influenzae antigens, H. influenzae type b, to S. pneumoniae (serotypes 3, 6B, 9N, 23F) vaccine-specific polysaccharide as well as polysaccharide complex antigens were measured by using ELISA developed by us. Statistical processing was carried out by methods of descriptive, parametric and nonparametric statistics by using Statistica 5.0 software.Results. Vaccination with Pneumo 23 was accompanied by IgG production against serotypes 3, 6, 9N, 23F-derived polysaccharide. A markedly increased anti-serotype 3 and 23F antibody level was observed 6 months after vaccination. Moreover, a significant increase in anti-polysaccharide 23F and anti-vaccine-derived polysaccharide IgM levels was found 1 month after the onset. In addition, anti-serotype 6B and 9N IgM antibodies were maintained 18 months after vaccination at high level, whereas it was significantly elevated against serotypes 3, 23F. Assessing an effectiveness of vaccine prophylaxis against Hemophilus type b infection, it was shown that a significantly increased anti-vaccine-derived polysaccharide IgM level was found 1, 6, 18 months after Act-HIB vaccination. In addition, IgG to the anti-H. influenzae type b polysaccharide tended to rise 1 month after the vaccination.Summary. Children with chronic bronchopulmonary diseases vaccinated by Pneumo-23 and Act-HIB demonstrated activated adaptive immunity manifested by increased vaccine-derived antigen-specific IgM and IgG antibodies.